1995
DOI: 10.1038/eye.1995.62
|View full text |Cite
|
Sign up to set email alerts
|

On the pathology of the iridocorneal-endothelial syndrome: The ultrastructural appearances of ‘subtotal-ICE’

Abstract: SUMMARYThe iridocomeal-endothelial syndrome (ICE syn The iridocorneal-endothelial syndrome (ICE syn drome) is characterised by a 'hammered-silver' appearance of the corneal endothelium, corneal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Many clinicopathological studies have described the microstructural pathological changes of ICE syndrome, which can be summarized as: alterations in the endothelial cell size, shape and density, with prominent apical surface abnormalities such as microvilli, filipodia and ‘blebs’, and a tendency to divide and develop into multiple endothelial layers 13,14 . Unsurprisingly, the observations of the endothelium in the current study are generally consistent with previously published specular or confocal microscopical descriptions, as well as with ex vivo in situ characteristics 5,10,14−16 . However, in this study we suggested that in vivo confocal microscopy may not only be used to diagnose ICE syndrome, but may be superior to specular microscopy in defining this diagnosis, especially in cases of marked corneal oedema and particularly in regard to the facility to image all corneal layers in detail and accurately measure cellular and subcellular structures using proprietary software 2,5,12,17 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Many clinicopathological studies have described the microstructural pathological changes of ICE syndrome, which can be summarized as: alterations in the endothelial cell size, shape and density, with prominent apical surface abnormalities such as microvilli, filipodia and ‘blebs’, and a tendency to divide and develop into multiple endothelial layers 13,14 . Unsurprisingly, the observations of the endothelium in the current study are generally consistent with previously published specular or confocal microscopical descriptions, as well as with ex vivo in situ characteristics 5,10,14−16 . However, in this study we suggested that in vivo confocal microscopy may not only be used to diagnose ICE syndrome, but may be superior to specular microscopy in defining this diagnosis, especially in cases of marked corneal oedema and particularly in regard to the facility to image all corneal layers in detail and accurately measure cellular and subcellular structures using proprietary software 2,5,12,17 .…”
Section: Discussionsupporting
confidence: 91%
“…Iridocorneal endothelial syndrome is an uncommon and, unfortunately, often under‐diagnosed condition, due to the variability of severity of presentation. Many clinicopathological studies have described the microstructural pathological changes of ICE syndrome, which can be summarized as: alterations in the endothelial cell size, shape and density, with prominent apical surface abnormalities such as microvilli, filipodia and ‘blebs’, and a tendency to divide and develop into multiple endothelial layers 13,14 . Unsurprisingly, the observations of the endothelium in the current study are generally consistent with previously published specular or confocal microscopical descriptions, as well as with ex vivo in situ characteristics 5,10,14−16 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These diagnoses were supported by endothelial specular microscopy (ESP). This method had previously been advocated as providing a definitive diagnosis of ICE syndrome,13 but at present ICE has been shown to have pleomorphic manifestations on ESP 14. It may be that ring melanoma deposits on the corneal endothelium mimic the in vivo ESP appearance of ICE cells during one of its transitional stages.…”
Section: Discussionmentioning
confidence: 99%